Five years of Trials. - Altman, D; Hrynaszkiewicz, I; Furberg, C; Grimshaw, J; Rothwell, P (2011)
This editorial marks the launch of a special collection of articles highlighting 'Five years of Trials' (http://www.trialsjournal.com/series/5years). The journal's achievements on its objectives since 2006 are described and some of the challenges still ahead are outlined - in particular further innovating in the reporting of trials and the publication of negative results. The other articles in this series are examples of where Trials has demonstrated progress on its objectives. These include the publication of raw data, extended versions of previously published trial-related articles, descriptions of 'lessons learned', negative results, and educational articles regarding ethics and reporting bias.